Peran Penyuluh Agama Dalam Mencegah Prilaku Agresif Remaja Di Desa Bayung Kepahiang - Rosa Amalia, Amanda; Mutiah, Mutiah; Zubaidah, Zubaidah; Yusniarti, Nela; Krismonia, Timi (Yayasan Darussalam Bengkulu, 2023)
Emotional development in adolescence is a critical period in individual development. Aggressive behavior refers to intentional actions with the purpose of causing harm or injury to others. Adolescence is a critical phase that connects childhood with adulthood. Researchers conducted observations and interviews in Bayung Village, Kepahiang. With the aim of getting some accurate information and how the role of religious instructors in preventing aggressive behavior in adolescents there. The research conducted used a qualitative approach that refers to a research process that collects descriptive data both orally and in writing about individuals and observed behavior. The research was conducted using purposive sampling technique, which is a technique taken by setting certain characteristics in the selection of informants. In this study, researchers took 2 informants in Bayung Village, Kepahiang. With criteria, including: 1) extension workers who have overcome teenagers with aggressive behavior, 2) extension workers who have provided material in the form of preventing children who have aggressive behavior, 3) teenagers who behave aggressively. Based on interviews with religious counselors in Bayung Village, Kepahiang, several conclusions can be drawn regarding the role of religious counseling in preventing aggressive behavior in adolescents. Religious counseling provides a deep understanding of the moral and ethical values taught in religious teachings.